Forgiveness, Gratitude, and Happiness among College Students - Triantoro Safaria (Intelektual Pustaka Media Utama, 2014)
Wellbeing is the ultimate goal for everyone, not only for adolescence. Present study explore the relationship between gratitude and forgiveness with happiness among college student. A total of 81 undergarduate psychology students were recruited in this study from a private university in Jogjakarta. 29.6% (24) of the sample were males and 70.4% (57) were females Regression analysis was used to predict the model. This model regression predict relationship between gratitude and forgiveness with happiness, explaining 28.9% of the variance (Adjusted R2= 0.289).Gratitude give the biggest contribution to happiness (b= .536 p= .000), but forgiveness has no significance relationship to happiness (b= .078, p= .414). This result means that gratitude is an important factor contribute to happiness among undergraduate student in this sample. The implication of study are discussing further.